ANALISIS PENENTUAN CORE BUSINESS PADA MASTERPLAN KAWASAN EKONOMI KHUSUS MEKAR PUTIH DI KABUPATEN KOTABARU - FADEL MUHAMMAD; MUHAMMAD EFFENDI (PPJP Universitas Lambung Mangkurat, 2019)
Fadel Muhammad (2019). Core Business Determination Analysis in the master plan of the Mekar Putih Special Economic Zone in Kotabaru Regency Advisor : Drs Muhammad Effendi, MSThis study aims to (1) To find out what factors are considered in determining the Core Business in the Mekar Putih Special Economic Zone Masterplan in Kotabaru Regency, (2) To determine perceptions government, private sector. and the community in the Core Business choice of the Mekar Putih Special Economic Consultation Masterplan in Kotabaru Regency, (3) To analyze what Core Business is suitable to be developed in the Mekar Putih Special Economic Zone Masterplan in Kotabaru District.Respondents in this study were 5 respondents from local government, 5 respondents from the private sector, 14 respondents from community leaders and institutions and 95 respondents from the community. The method used in processing data is the AHP (Analytical Hierarchy Process) method. and Descriptive Quantitative The results of this study indicate that the choice of regional government for Core Business in the Mekar Putih Special Economic Zone Master Plan is the Core Business Industri 67% and Tourism Core Business 33%, and the choice of private parties for Core Business in the Mekar Putih Special Economic Zone Masterplan Business Industri 80% and Core Business Tourism 20%, for community leaders and community institutions for the determination of Core Business in the Mekar Putih Special Economic Zone Masterplan is the 57% Core Business Industri and 43% Core Business Tourism and the general public in determining Core Business is Core Business Industri 81% and Tourism Core Business 19% With the most dominant conclusion is Industrial Core Business which is the main activity in the White Blooms Special Economic Zone.Keywords: Core Business, Special Economic Zones. Perception of Local Government, Private Sector and Society, AHP Method, Quantitative Descriptive